Structure and photoluminescence of helium-intercalated fullerite C60 - Legchenkova, I. V.; Silaeva, N. B.; Zoryansky, V. N.; Zinoviev, P. V.; Eremenko, V. V.; Avdeenko, A. A.; Yagotintsev, K. A.; Strzhemechny, M. A.; Stetsenko, Yu. E.; Prokhvatilov, A. I.; Ruoff, R. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Intercalation of C60 single crystals with helium was studied by powder x-ray diffractometry. It was established that the intercalation is a two-stage process, octahedral cavities are filled first and then tetrahedral ones, the chemical pressure being negative during both stages. For the first time low-temperature (5 K) photoluminescence spectra of helium-intercalated fullerite C60 were studied. The presence of helium in lattice voids was shown to reduce that part of the luminescent intensity which is due to the emission of covalently bound pairs of C60 molecules, the socalled "deep traps" with the 0-0 transition energy close to 1.69 eV. The mechanism of the effect of the intercalation with helium on the pair formation in fullerite C60 is discussed.